USP1-WDR48 deubiquitinase complex enhances TGF-β induced epithelial–mesenchymal transition of TNBC cells via stabilizing TAK1 - Han, Dianwen (Cell Cycle, 2021)
Triple-negative breast cancer (TNBC) is the most aggressive histological subtype of breast cancer and is characterized by poor outcomes and a lack of specific-targeted therapies. Transforming growth factor-β (TGF-β) acts as the key cytokine in the epithelial–mesenchymal transition (EMT) and the metastasis of TNBC. However, the regulatory mechanisms of the TGF-β signaling pathway remain largely unknown. In this study, we identified that the USP1/WDR48 complex could effectively enhance TGF-β-mediated EMT and migration of TNBC cells. Furthermore, lower phosphorylation of Smad2/3, Erk, Jnk, and p38 was noted on the suppression of the expression of endogenous USP1 or WDR48. Moreover, the USP1-WDR48 complex was found to downregulate the polyubiquitination of TAK1 and mediate its in vitro stability. Therefore, our findings have shed a light on the novel role of the USP1/WDR48 complex in promoting TGF-β-induced EMT and migration in TNBC via in vitro stabilization of TAK1.